Penggunaan Model Pembelajaran Science Environment Technology and Society (Sets) untuk Meningkatkan Kemampuan Berpikir Kritis dan Sikap Ilmiah - Maimunah Maimunah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2016)
This study aimed to determine the improvement of critical thinking skills and student’s scientific attitudes on the colloidal material by applying the learning model science environment technology and society (SETS). The method was used in this study is quasi-experimental research design "Pretest-Posttest Nonequivalent Control Group Design". The sample in this study was a class XI student at one of SMAN in Majalengka, with totaling 62 students. Data collected through a written test and observation sheets. The results showed that SETS learning for colloidal material can enhance student’s critical thinking skills with N-Gain of 42% (moderate category) and the student’s scientific attitude was 72,7 % (excellent category). Increasing student’s critical thinking skills class experiment also differed significantly from the control class. Thus, learning chemistry with SETS learning model should be developed for the implementation of SETS learning can improve critical thinking skills and students’ scientific attitudes. Keywords: colloidal systems, critical thinking skills, science environment technology and society (SETS), scientific attitude.